Daya Tarik Wisata Ruang Terbuka Hijau di Jakarta Utara - Respati, Diva Teguh (REKSABUMI, 2025)
North Jakarta has 8.95 km² of green open space (RTH), representing 6.11% of its total area. This figure falls well below the minimum 30% RTH requirement for urban areas. One way to increase RTH is by stimulating public demand. Therefore, the functions of RTH must be maximized—not only in terms of ecology but also by embracing tourism roles.This article aims to analyze the tourism appeal of RTH in North Jakarta. The analysis employs the 4A framework (attraction, accessibility, amenity, ancillary), storynomics, special-interest tourism, and visitation rates. These components are used to assess RTH’s attractiveness and potential as tourism destinations. A qualitative analysis was conducted on existing RTH, and strategies were developed for tourism development in both current and planned RTH. Based on the findings, 40% of RTH in North Jakarta exhibit tourism potential, accompanied by rising visitation rates. These results highlight strong public demand for RTH with tourism appeal.